Tradition Fast White in Islamic Law - Dhinda Pradnya Paramitha (International Journal of Islamic Educational Research, 2024)
This research explains the practice of fasting in the context of Islamic law, identifying the views of Islamic scholars and literature regarding fasting. The aim of this research is to provide comprehensive insight into the practice of fasting and its relevance in Islamic teachings. The research method used is a qualitative approach by analyzing related texts and literature, such as the Al-Qur'an, Hadith, views of ulama, and previous research. The research results show that mutih fasting is a tradition that is still maintained by some Javanese people, especially before weddings. Even though it has no direct basis in Islamic law, mutih fasting is carried out with the aim of gaining inner peace and physical and spiritual readiness before marriage. The procedure for white fasting involves consuming only white foods and drinks, such as white rice and water, as well as increasing worship such as prayer, dhikr and supplication. However, the analytical views of Islamic scholars and law show that fasting is not recommended in Islamic teachings and is not included in the worship exemplified by the Prophet Muhammad SAW. Although it is permissible if the intention is solely for Allah SWT, mutih fasting is more cultural than religious. The recommendation for Muslims is to carry out this tradition carefully and ensure that their intentions are truly for Allah SWT. In conclusion, fasting mutih before a wedding is a tradition that is more embedded in Javanese culture than Islamic religion. Although it is not prohibited, this practice should be carried out with clear intentions and does not conflict with Islamic teachings. Further research is needed to bring closer understanding between local culture and pure Islamic teachings.